Utilization of Cyber Extension Media as a Source of Information by Agricultural Extension Workers in Kupang Regency - Bulkis, Bulkis (Universitas Syiah Kuala, 2023)
Agriculture is one of the important sectors for a country because this sector is able to provide basic needs for its people. Developed countries currently control the agricultural sector. Increasingly, the fulfillment of basic needs in the community has increased. The objectives of this study are, Explaining the characteristics of extension workers, media use, stages of information search in Cyber Extension in Agricultural Extension in Kupang Regency, Analyzing the relationship between extension characteristics and information search stages in Cyber Extension, Analyzing the relationship between media use and information search stages in Cyber Extension in Kupang District. This study is designed as a correlational descriptive census research. The variables studied in this study are the characteristics of extension workers (X1), media use (X2), stages of information search (Y1). The results of this study are the characteristics of extension workers on age indicators, level of media ownership and motivation are significantly related to the stages of information search. The fluency of extension workers in the information search stage is supported by age, level of media ownership and motivation of extension workers. The stages of information search on the Starting, Chaining, Browsing, Differentiating, Monitoring, and Extracting indicators are positively and tangibly related to the use of Cyber Extension in information benefit indicators. The ability of extension workers in utilizing Cyber Extension will be supported by the smoothness of extension workers in carrying out the information search stages